2020
DOI: 10.1002/acp.3665
|View full text |Cite
|
Sign up to set email alerts
|

Liars are perceived as more credible than truth‐tellers who recall a repeated event

Abstract: Recurring forms of abuse like domestic violence are unfortunately common. When an individual makes an allegation about their experience, however, there is rarely additional evidence to corroborate their claim. The veracity of the allegation is thus likely to be a central concern in subsequent proceedings. This experiment explored evaluator's perceptions of adults who were lying, or truthfully recalling a repeated event. In this experiment, participants observed a filmed interview of a speaker recalling an even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
7
2
Order By: Relevance
“…Third, the credibility of a complainant’s testimony is often scrutinized by factfinders (e.g., police) and trier of facts. Given the potential difficulties repeated-event complainants might face in recalling particular instances, it is possible that their testimony could appear less credible than single-event complainants (e.g., Deck & Paterson, 2020; Weinsheimer, Coburn, Chong, MacLean, & Connolly, 2017). To counteract such negative consequences, researchers should continue to investigate ways of supporting recall of repeated events.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the credibility of a complainant’s testimony is often scrutinized by factfinders (e.g., police) and trier of facts. Given the potential difficulties repeated-event complainants might face in recalling particular instances, it is possible that their testimony could appear less credible than single-event complainants (e.g., Deck & Paterson, 2020; Weinsheimer, Coburn, Chong, MacLean, & Connolly, 2017). To counteract such negative consequences, researchers should continue to investigate ways of supporting recall of repeated events.…”
Section: Discussionmentioning
confidence: 99%
“…As the results of both experiments indicate that Reality Monitoring cannot effectively distinguish the veracity of repeated-event speakers, we remain reliant upon evaluators' subjective credibility assessments. This reliance is concerning given that repeated-event witnesses are unlikely to be perceived as high in credibility (e.g., Deck & Paterson, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, up to 50% of laypeople believe that claims of domestic violence are often fabricated or exaggerated to improve the outcome of custody disputes (VicHealth, 2014). Alarmingly, laboratory studies have found that laypeople perceive witnesses who truthfully recall a repeated event as less credible than those who recall a single event (Connolly, Price, Lavoie, & Gordon, 2008; Weinsheimer, Coburn, MacLean, & Connolly, 2017), and even less credible than liars (Deck & Paterson, 2020b). Although the rates of false allegations for events like domestic violence appear to be low (Melville & Hunter, 2001), false allegations can occur, with devastating consequences for the accused.…”
mentioning
confidence: 99%
“…A community sample viewed children who reported a repeated play session as less credible than those who reported a single session, although this effect may have been driven by inconsistencies within the former’s accounts rather than frequency of experience, per se ( Connolly et al, 2008 ). Similarly, adults who reported a repeated event have been perceived as less cognitively competent, honest, and credible compared to adults who reported a single event (food-tasting event; Weinsheimer et al, 2017 ), and less credible compared to adults reporting either a single event or a lie (healthy lifestyle session; Deck & Paterson, 2020 ). However, the effect of event frequency may depend upon the veracity of the speaker ( Deck & Paterson, 2021 ).…”
Section: Event Frequencymentioning
confidence: 99%